Measuring Forest Biodiversity Status and Changes Globally - Hill, Samantha L. L.; Arnell, Andy; Maney, Calum; Butchart, Stuart H. M.; Hilton-Taylor, Craig; Ciciarelli, Carolyn; Davis, Crystal; Dinerstein, Eric; Purvis, Andy; Burgess, Neil D. (Frontiers in Forests and Global Change, 2019)
The world’s forests are crucially important for both biodiversity conservation and climate mitigation. New forest status and forest change spatial layers using remotely sensed data have revolutionised forest monitoring globally, and provide fine-scale deforestation alerts that can be actioned in near-real time. However, existing products are restricted to representing tree cover and do not reflect the considerable spatial variation in the biological importance of forests. Here we link modelled biodiversity values to remotely sensed data on tree cover to develop global maps of forest biodiversity significance (based on the rarity-weighted richness of forest mammal, bird, amphibian and conifer species) and forest biodiversity intactness (based on the modelled relationship between anthropogenic pressures and community intactness). The strengths and weaknesses of these products for policy and local decision-making are reviewed and we map out future improvements and developments that are needed to enhance their usefulness.